Semiempirical, parameterized spectrum estimation for x‐ray computed tomography. Issue 5 (16th March 2021) - FitzGerald, Paul; Araujo, Stephen; Wu, Mingye; De Man, Bruno
Abstract : Purpose: To develop a tool to produce accurate, well‐validated x‐ray spectra for standalone use or for use in an open‐access x‐ray/CT simulation tool. Spectrum models will be developed for tube voltages in the range of 80 kVp through 140 kVp and for anode takeoff angles in the range of 5° to 9°. Methods: Spectra were initialized based on physics models, then refined using empirical measurements, as follows. A new spectrum‐parameterization method was developed, including 13 spline knots to represent the bremsstrahlung component and 4 values to represent characteristic lines. Initial spectra at 80, 100, 120, and 140 kVp and at takeoff angles from 5° to 9° were produced using physics‐based spectrum estimation tools XSPECT and SpekPy. Empirical experiments were systematically designed with careful selection of attenuator materials and thicknesses, and by reducing measurement contamination from scatter to <1%. Measurements were made on a 64‐row CT scanner using the scanner's detector and using multiple layers of polymethylmethacrylate (PMMA), aluminum, titanium, tin, and neodymium. Measurements were made at 80, 100, 120, and 140 kVp and covering the entire 64‐row detector (takeoff angles from 5° to 9°); a total of 6, 144 unique measurements were made. After accounting for the detector's energy response, parameterized representations of the initial spectra were refined for best agreement with measurements using two proposed optimization schemes: based on modulation and based on gradient descent. X‐ray transmission errors were computed for measurements vs calculations using the nonoptimized and optimized spectra. Half‐value, tenth‐value, and hundredth‐value layers for PMMA, Al, and Ti were calculated. Results: Spectra before and after parameterization were in excellent agreement (e.g., R 2 values of 0.995 and 0.997). Empirical measurements produced smoothly varying curves with x‐ray transmission covering a range of up to 3.5 orders of magnitude. Spectra from the two optimization schemes, compared with the unoptimized physic‐based spectra, each improved agreement with measurements by twofold through tenfold, for both postlog transmission data and for fractional value layers. Conclusion: The resulting well‐validated spectra are appropriate for use in the open‐access x‐ray/CT simulator under development, the x‐ray‐based Cancer Imaging Toolkit (XCIST), or for standalone use. These spectra can be readily interpolated to produce spectra at arbitrary kVps over the range of 80 to 140 kVp and arbitrary takeoff angles over the range of 5° to 9°. Furthermore, interpolated spectra over these ranges can be obtained by applying the standalone Matlab function available at https://github.com/xcist/documentation/blob/master/XCISTspectrum.m .